Projectile velocity control on coilgun using genetic algorithms - Basuki Winarno; Rakhmad Gusta Putra; Indarto Yuwono; Bambang Sumantri; Agus Indra Gunawan (Institute of Advanced Engineering and Science, 2019)
Multistage Coilgun is an electromagnetic coil composed of more than one coil so that can throw a projectile. The velocity of the projectile coming out of the tube must be controlled. The mechanism can be done by a multistage coilgun design that has a varying number of turns. Each coil that coincides with one another is wrapped separately. The motion of projectile following the velocity profile is perfomed by designing a multistage coil in different layer number based on the energy needed, and therefore the coil is more efficient. Furthermore, the velocity of the projectile is controlled by controlling the current injected to the coil using the Genetic Algorithm method. A prototype of a multistage coilgun system with the proposed coil variation is built in this work. The test is carried out 7 times with an average final velocity of the projectile of 29,89 m/s. While the results of the numerical simulation are 32,63 m/s. Testing error compared to simulation is 9,15%.